Does diet affect morphological parameters of Neoseiulus tunas (De Leon) (Acari: Phytoseiidae)? - Ferreira, Mizael de Melo [UNESP] (2021)
Neoseiulus Hughes is one of the most diverse genus of Phytoseiidae, with approximately 400 described species. Among them, Neoseiulus tunus (De Leon) is very frequent and abundant in the Neotropical region. Although considerable amount of data about morphological variation of phytoseiid mites are available, the possible causes of intraspecific variations are still poorly understood, being diet and feeding habit usually reported as the main drivers. The present study investigated the influence of three different diets on morphological traits of taxonomic interest of N. tunus, aiming to verify whether diet is a determinant factor in the morphological pattern of this species and which structures are most affected by them. Our results show that based on the diet treatment, populations of N. tunus may be differentiated based on the size of morphological traits. All treatments differ from stock population and among them, except between populations feeding with Aculops lycopersici (Massee) (Eriophyidae) and Tetranychus urticae (Kock) (Tetranychidae). The widest range occurred on the dorsal setae, macrosetae of leg IV, width of the dorsal shield, distance between the bases of the genital's setae and posterior width of the ventrianal shield. Most of the dorsal setae responded to the treatment with significant variation, being the longest lengths observed when the A. lycopersici was offered as diet. Considering the other two diets, the variation does not present a clear increasing or reducing pattern.